The impact of nutritional interventions on child health and cognitive development - Bommer, Christian; Mittal, Nitya; Vollmer, Sebastian (Annual review of resource economics, 2020)
Despite growing policy commitment and decades of extensive research, nutritional deficiencies remain a key challenge for health systems worldwide. In addition to causing significant personal costs for those affected, indirect effects, such as reduced overall human capital accumulation or losses in labor productivity, can impose substantial obstacles for the achievement of economic development goals. This review provides an overview of the impact of key interventions aiming to improve nutritional intake in order to reach better physical health and cognitive outcomes among children in developing countries. We argue that, although promising interventions exist, malnutrition is a complex problem, likely requiring a stronger focus on multifactorial approaches. Moreover, more research is necessary to maximize compliance and sustainability if interventions are to successfully transform into large-scale policy programs. We further discuss the emerging double burden of malnutrition as a key challenge for policy makers in resource-poor settings.
Gesehen am 10.12.2020
Keywords: Aufsatz in Zeitschrift